Foraging for Coherence in Neuroscience: A Pragmatist Orientation. - Schulkin, Jay (Contemporary Pragmatism, 2016)
Foraging for coherence is a pragmatist philosophy of the brain. It is a philosophy anchored to objects and instrumental in understanding the brain. Our age is dominated by neuroscience. A critical common sense underlies inquiry including that of neuroscience. Thus a pragmatist orientation to neuroscience is about foraging for coherence; not overselling neuroscience. Foraging for coherence is the search for adaptation - diverse epistemic orientation tied ideally to learning about oneself, one's nature, and one's history in the context of learning about the brain. Neuroscience is about us: Our desires, habits, styles of reason, human vulnerability, and abuse. The language of the neuron, Foraging for coherence is a pragmatist philosophy of the brain. It is a philosophy anchored to objects and instrumental in understanding the brain. Our age is dominated by neuroscience. A critical common sense underlies inquiry including that of neuroscience. Thus a pragmatist orientation to neuroscience is about foraging for coherence; not overselling neuroscience. Foraging for coherence is the search for adaptation - diverse epistemic orientation tied ideally to learning about oneself, one's nature, and one's history in the context of learning about the brain. Neuroscience is about us: Our desires, habits, styles of reason, human vulnerability, and abuse. The language of the neuron, or the gene, or the systems does not replace the discussion about us as the person, in the social and historical context.